2020
DOI: 10.1186/s12993-019-0164-0
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism in cognitive disorders in a murine model of neuropathic pain

Abstract: Background: A sex-difference in susceptibility to chronic pain is well-known. Although recent studies have begun to reveal the sex-dependent mechanisms of nerve injury-induced pain sensitization, sex differences in the affective and cognitive brain dysfunctions associated with chronic pain have not been investigated. Therefore, we tested whether chronic pain leads to affective and cognitive disorders in a mouse neuropathic pain model and whether those disorders are sexually dimorphic. Methods: Chronic neuropat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…There were no differences at baseline between mechanosensitivity (spinal reflex thresholds) and emotional-affective responses (vocalizations), but females exhibited increased baseline anxiety-like behavior (OFT) compared to males in both the untreated and sham-treated control groups (see Figures 3D and 4D). This confirms findings from the literature that males spent the same or increased time in the center of the OFT compared to females at baseline [3,98], though one study found no sex difference in OFT anxiety-like behavior in a chronic spinal nerve transection pain model [99]. FE+ and FE− phenotypes showed differences in the magnitude of emotional-effective responses not only in the neuropathic pain model, as we previously reported [42], but also in the arthritis pain model (see Figure 3B,C and Figure 4B,C).…”
Section: Discussionsupporting
confidence: 87%
“…There were no differences at baseline between mechanosensitivity (spinal reflex thresholds) and emotional-affective responses (vocalizations), but females exhibited increased baseline anxiety-like behavior (OFT) compared to males in both the untreated and sham-treated control groups (see Figures 3D and 4D). This confirms findings from the literature that males spent the same or increased time in the center of the OFT compared to females at baseline [3,98], though one study found no sex difference in OFT anxiety-like behavior in a chronic spinal nerve transection pain model [99]. FE+ and FE− phenotypes showed differences in the magnitude of emotional-effective responses not only in the neuropathic pain model, as we previously reported [42], but also in the arthritis pain model (see Figure 3B,C and Figure 4B,C).…”
Section: Discussionsupporting
confidence: 87%
“…A recent study reported that cognitive deficit measured with the Morris water maze and novel object location test were seen only in male mice, but not in female mice in the L5 spinal nerve transection model of neuropathic pain 52 . While our current study showed that the SNI-induced pathological changes, including increase in circulating leukocytes (Figures 1 A, B and S3A, B), brain PVMs (Figures 2 , S3C, and S4), and gliosis (Figures 4 and S4D, E), the elevation of plasma CXCL12 (Figure 6 A-D) and SNI-induced cognitive impairment were not different between male and female mice.…”
Section: Discussionmentioning
confidence: 98%
“…There has been reported a link between neuropathic pain (including diabetic neuropathy) and cognitive deficits in rodents (Kodama et al, 2011;Shiers et al, 2018;Boccella et al, 2019;Liang et al, 2020;Won et al, 2020) and humans (Curatolo et al, 2017;Ojeda et al, 2018;Naranjo et al, 2019). However, current therapies for neuropathic pain have not considered this relationship.…”
Section: Cognitive Deficitsmentioning
confidence: 99%